TEACHERS’ INSTRUCTIONAL STRATEGIES IN DEVELOPING EARLY CHILDHOOD CREATIVITY; INSIGHTS FROM GRADATION COLOURING ACTIVITIES - Firda Indana Zulfa; Moch. Maulana Trianggono; Firman Ashadi (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
Teachers play a central role in designing instructional strategies that stimulate children’s creativity through engaging and developmentally appropriate activities. One such pedagogical approach is the use of gradation colouring, which not only introduces children to artistic techniques but also enhances cognitive flexibility, imagination, and aesthetic sensitivity. This study therefore aims to investigate teachers’ instructional strategies in fostering children’s creativity through gradation colouring activities. Using a qualitative case study design, data were collected through classroom observations, in-depth interviews with teachers, and supporting documentation. The data were analyzed using Miles and Huberman’s which involves data reduction, data display, and conclusion. The findings reveal that teachers employed various strategies, such as scaffolding techniques, direct and visual approach, motivation through fun activities, giving freedom to experiment, and providing positive and constructive feedback. Thus, the instructional strategies implemented by teachers through color gradation activities have a significant positive impact on the development of early childhood creativity. Therefore, color gradation activities are not only an art technique but also an effective approach to support the holistic creative development of children.